1995
DOI: 10.1016/0014-5793(95)01046-h
|View full text |Cite
|
Sign up to set email alerts
|

N‐Glycosylation‐defective receptor for erythropoietin can transduce the ligand‐induced cell proliferation signal

Abstract: . apacity by the epidermal growth factor receptor is glycosylaion-dependent [6,7]. N-Glycosylation at a specific site of the nsulin receptor fl subunit appears to be important for the eceptor activation and transmembrane signaling [4,5]. Degly-:osylation of the basic fibroblast growth factor receptor results n the loss of the ligand-binding [8] and sialylation of the Ninked sugars in the somatostatin receptor is required for mainenance of the high-affinity binding state [9].EPO transduces the proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The N-glycosylation site per se is not sufficient to provide this advantage, because residues s46 -57 containing the Nglycosylation site did not improve EPO-R maturation to the same extent. In that respect, impaired N-glycosylation of EPO-R (46,47) had no measurable effect on cell-surface EPO-R levels, EPO binding kinetics, and EPO-induced cell proliferation. Carbohydrates attached to proteins play a role in multiple biochemical pathways including folding, stability, targeting, and clearance of proteins (48).…”
Section: Er Exit and Intracellular Traffickingmentioning
confidence: 92%
“…The N-glycosylation site per se is not sufficient to provide this advantage, because residues s46 -57 containing the Nglycosylation site did not improve EPO-R maturation to the same extent. In that respect, impaired N-glycosylation of EPO-R (46,47) had no measurable effect on cell-surface EPO-R levels, EPO binding kinetics, and EPO-induced cell proliferation. Carbohydrates attached to proteins play a role in multiple biochemical pathways including folding, stability, targeting, and clearance of proteins (48).…”
Section: Er Exit and Intracellular Traffickingmentioning
confidence: 92%
“…Glycosylation is thought to play a role in controlling EpoR cell surface expression. N-glycosylation-defective EpoR can still transduce the ligand-induced cell proliferation signal, but the level of expression of this mutant EpoR on the cell surface is significantly reduced [35]. Similar findings were obtained when the N-glycosylation inhibitor tunicamycin was used [36].…”
Section: The Erythropoietin Receptorsupporting
confidence: 70%
“…Previous studies have shown that inhibition of glycosylation by tunicamycin treatment leads to a decrease in the total number of Epo binding sites [36]. However, other studies suggested that glycosylation is not required for EpoR surface expression and signal transduction [35,36]. These studies used transfected forms of EpoR and not endogenous EpoR.…”
Section: Studies On Epor Have Gained Popularity Recently Because Of Tmentioning
confidence: 99%
“…First, since our in silico geometrical prediction and in vitro SPR analysis were based on only extracellular domains of EPORs, it is unclear how peptide binding induces the geometric event of membrane-spanned full-length EPOR. Second, endogenous EPOR, which would respond to our peptides, could be extracellularly glycosylated [ [61] , [62] , [63] ]. Although this glycosylation has been known to enhance the extracellular trafficking of EPOR rather than the binding affinity of EPO, its effect on binding with our peptides still remains in question.…”
Section: Discussionmentioning
confidence: 99%